Developing Geospatial-based Land grading information System: A Case of Adama City, Oromia, Ethiopia - Wondosen, Negash (ASTU, 2024)
Land grading is a pivotal aspect of land use planning, infrastructure development, and urban growth management. Its purpose is to assess and modify the topography of land to ensure its suitability for various purposes, including residential, commercial, agricultural, or industrial use. The reliance on traditional manual assessments in land grading processes introduces inconsistencies and inefficiencies that can compromise the suitability of land for different purposes. Developing a GIS-based land grading system that utilizes geospatial data and analysis The general objective of the research is to analyze land grading system of Adama city using geospatial technology. The general objective of the research is to analyze land grading system of Adama city using geospatial technology. The data collection phase involves gathering various geospatial data sources essential for land grading assessments, such as topographic DEM, aerial imagery, land cover information, infrastructure data and any other relevant datasets. It is crucial research is to analyze land grading system of Adama city using geospatial technology. Data Analysis Techniques carried out using AHP and weight overlay methods. The indicators and their correlation for analyzing with the techniques of AHP are asphalt road is of equal importance to asphalt road, water supply is of equal importance to water supply, electric supply is of equal importance to electric supply, educational centers is of equal importance to educational centers, health centers is of equal importance to health centers and DEM is of equal importance to DEM. Buffering and rastering are the analysisi procedures the map overlayed produced as a result ,which shows the hih,medim,moderate and less land grading.In a broader context, map overlay refers to combining the attributes of intersecting features represented in two or more georegistered data layers.
Keywords: Land grade, AHP, weight overlay